Assessment of fire behaviour of high‐speed trains' interior materials: small‐scale and full‐scale fire tests. (13th December 2013) - Capote, Jorge A.; Jimenez, José A.; Alvear, Daniel; Alvarez, Julio; Abreu, Orlando; Lazaro, Mariano
SUMMARY The development of fire‐safety measures for high‐speed passenger trains has been focused on preventing fire initiation or delaying fire growth and spread through small‐scale tests of the materials used in trains. However, new fire‐safety approaches for trains consider a systemic approach. This approach considers numerous global factors that influence fire dynamics, such as the influence of vehicle design, selection of materials, and active and passive protection systems installed. In the present paper, the results of small‐scale and full‐scale tests carried out on the new generation of high‐speed trains operating in Spain are presented. This rolling stock is classified as category B according to the Technical Specification for Interoperability and Operation Category 3 according to EN 45545–1. The results confirmed good fire behaviour using both approaches (small and full‐scale tests). Additionally, several analyses have been performed, including an analysis of the quality of materials used for making different components of the passenger compartment and the influence of ignition source position on fire development. Copyright © 2013 John Wiley & Sons, Ltd.